Manajemen Kesehatan Ternak Sapi Bali Di Distrik Bobonaro, Timor Leste - Gomez, Marito Britos; Sanam, Maxs U.E; Winarso, Aji (Jurnal Veteriner Nusantara, 2024)
Bali cattle (Bos sondaicus) raising is one of the cornerstones of economic development in Timor Leste. A sound livestock health manajement is needed to be successful in bali cattle raising .This study aimed to describe the health management adopted by bali cattle raisers in one of the districts in Timor Leste. This is a descriptive survey using questionnaires, interviews and direct observation. The sampling method uses the Cluster Random Sampling technique. The sample in this study consisted of 282 farmers in 6 districts (Maliana District, Lolotoe District, Balibo District, Bobonaro District, Atabae District, and Kailaco District) located in the Bobonaro District. The data obtained were then analyzed by descriptive statistical analysis using distribution tables. From bali catle management, feeding and drinking’s perspective, the results showed that most cattle raisers adopted semi-intensive raising system (58%), free grazing (79.08%), the feed given is green / grass feed (100%), namely natural grass originating from fields (85.11%) and drinking water sources derived from pond and river (35.11%). From a viewpoint of the health management (treatment, prevention and control of disease), the results indictated that most sick animals are not treated (33.45%), livestock are often vaccinated (43.97%), pens are never sanitized (63.83%), if livestock die due to disease then the meat is often consumed (50.00%) The type of drug that is widely used is chemical drugs (59%). Treatment and vaccination are mostly done by veterinary paramedics (55.67% and 67.38%), however when seen from the awareness of the power of treatment measures, farmers prefer veterinarians (55.67%). In the aspect of reproductive status, the result showed that most cattle naturally mate (100%), gestational age is 9 months (93.62%), estrus post partum is 3 months (60.25%), calving interval is 12 months (75, 53%) and calf mortality age that is <2 months (69.15%).